Hubungan Regulasi Diri dalam Belajar dan Efikasi Diri dengan Prokrastinasi Akademik Mahasiswa - Indah Sari Liza Lubis (Faculty of Psychology, Universitas Medan Area, 2018)
This study aims to determine: (1) the relationship between self regulated learning and student academic procrastination; (2) the relationship of self efficacy with student academic procrastination; (3) the relationship between self regulated learning and self efficacy with student academic procrastination. The hypothesis proposed is a negative relationship between self regulated learning and self efficacy with student academic procrastination, assuming the higher self regulated learning and self efficacy, the lower the student academic procrastination. Conversely, the lower the self regulated learning and self efficacy, the higher the student's academic procrastination. The number of samples is 61 people. The sampling technique uses saturated sample techniques. The data collection techniq uses questionnaire. The research method used is quantitative methods. The results of the study conclude that: (1) there is a negative relationship between self regulated learning and student academic procrastination; (2) there is a negative relationship between self efficacy and student academic procrastination; (3) there is a negative relationship between self regulated learning and self efficacy with student academic procrastination.